Relationship between career future concern, personal goal orientation, and perceived social support to career adaptability among Malaysian vocational college - Zahari, Zulhazmi; Omar, Muhd Khaizer (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The swift of the boundary less technology advancement due to the expansion of Industrial Revolution 4.0 has indirectly impacted the national development and the employment trend. This situation has embarked concerns among educational stakeholders especially in Technical and Vocational Education and Training (TVET) stream to meet the industrial requirements. The graduates, in general, have received criticism due to their lackluster performance when entering job and this environment brings into serious matter in round table discussion especially issues related to graduates lack of skills, job mismatches, and lack of industrial participations. Far little attention has been paid on TVET streams, however, received astonish promotion due to political empowerment and government proactive action to combat lack of skilled-employees in the nation. This article frames the career adaptability as primal factors in synchronizing graduates workforce readiness with the employment landscape. The discussion leads to understanding the career adaptability dimension progression among Malaysian vocational college students. The relationship between selected variables of career future concern, personal goal orientation, perceived social support and career adaptability was investigated. The research was conducted using quantitative approach by self-administering questionnaire booklet and distributed to 226 students in six fields of study who are currently enrolling in Diploma program using purposive sampling technique. Descriptive and inferential statistics was utilized using SPSS Versions 23 to acquire the relationship based on the formulated research questions. Future direction towards understanding the relationship that may exist between career adaptability and the aforementioned variables will suggest evocative improvements in TVET curriculum implementation and rife among the coteries of TVET stakeholders who uphold the betterment for the future grassroots of the nation.